Patterns and predictors of smoking cessation among smokers attending smoking cessation clinics in Peninsular Malaysia - W.P Sh. Ezat,; A.A Selahuddeen,; S.M Aljunid,; Z Zarihah, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : This study seeks to identify the socio-demographic and behavioral characteristics of smokers (aged 18 and above), thus develop a predicting model for tobacco abstinence receiving cessation services for tobacco dependence at the Smoking Cessation Clinics (SCC) in government Primary Health Centers in Malaysia. These predictors would improve the effectiveness and efficiency of these clinics. Methods : Smokers who sought smoking cessation therapy at the SCCs from 1st January 2004 to 31st December 2004 were chosen randomly from clinic’s registries, and 254 smokers were recruited from 8 clinics chosen through stratified random sampling. Data analyses were performed with SPSS 12.0. 17.3% of smokers attending SCCs were able to quit smoking for at least six months. Results : Factors significantly contributing to quitting success were elderly smokers (above 40 years old), smoked for more than 15 years, smoked less than ten sticks per day, had a previous history of quitting attempt, self referral to the clinic, high confidence level, attended SCC at least four times, each counseling session lasted for at least 30 minutes and were satisfied with the clinic service. In logistic regression model, smokers aged 40 years and above were 6.7 times more successful to quit, high level of confidence were nine times more successful, smoked more than ten sticks per day were ten times less successful, self referred smokers were ten times more successful and attending for at least 30 minutes counseling session were 12 times more successful. Conclusion : This study concludes that more concerted effort is needed to approach various groups of target population and SCCs clinic services need to be improved.